Autumn Migration to Higher Latitudes in Seminole Bats (Lasiurus seminolus) Redefines Seasonal Ranges: Evidence From Stable Isotopes and Fatality Data From Wind Energy Facilities - Julia R. Wilson; Michael C. True; Caitlin J. Campbell (Ecology and Evolution)
ABSTRACT The linkages between individual migrations and population‐level distributions are essential for understanding ecological dynamics. Here we describe how an unconventional migratory strategy in the Seminole bat (Lasiurus seminolus) results in an extended autumn range, both north and west of its currently described range. Awareness of this redefined distribution will likely reduce possible misidentification with a similar species, the eastern red bat (L. borealis), during any form of monitoring for purposes of conservation and management efforts. At wind energy facilities during the autumn seasons of 2019–2022 in Iowa, Illinois, Indiana, Michigan, Ohio, and Maryland, we discovered 49 Seminole bat carcasses as fatalities in autumn. All were outside of the species' currently described range in the southeastern United States. For 10 carcasses, we confirmed species identification using molecular techniques. We then modeled the geographic origins of viable fur samples from 17 carcasses using stable hydrogen isotope analysis. Finally, we synthesized current and historical records of the species to redefine seasonal range boundaries. Genetic analysis confirmed that carcasses were Seminole bats, and stable isotope analysis revealed that all bats sampled had migrated north between summer and autumn, leaving the previously defined species range. Our seasonally explicit range delineation for Seminole bats shows that this species expands its range northward in summer and again expands its range in autumn to the north and west to a region that is 1.3 million km2 larger than previously recognized. Northward migration in autumn, and the corresponding range extension, were previously undetected in Seminole bats. Our findings also demonstrate that this species, like its congeners, is susceptible to wind turbine fatality. Although the breadth of conservation risk is unknown, this study highlights the importance of obtaining an accurate understanding of migratory movements and the distribution of species to aid in species identification, management, and conservation.